Avaliação das características demográficas, clínicas e polimorfismo genético como fatores de risco para o prolapso pélvico em mulheres brasileiras - Martins, Karina de Falco [UNIFESP] (2010)
Objective: To verify the possible association between the presence of the polymorphism in exon 31 of COL3A1 gene and the occurrence of genital prolapse in a sample of the population. Methods: case-control study involving 316 patients staged for pelvic organ prolapse, using the system for quantification of pelvic organ prolapse (POP-Q), standardized by the International Continence Society (ICS). The case group consisted of 107 patients with stage III and IV and the control group of 209 women at stages 0 and I. Was applied to these patients anamnesis, in order to assess the presence or absence of major risk factors for genital prolapse (obstetric history, age at menopause, family history, chronic cough and constipation). There was also, collecting 5 ml of peripheral blood leukocyte DNA extraction. The fragment to be studied (exon 31 of COL3A1 gene) was amplified by the polymerase chain reaction (PCR). To compare the qualitative variables we used the chi square (X2). For quantitative variables was chosen by the Mann - Whitney U, as these variables had normal distribution pattern in the population. For the calculation of odds ratios and confidence intervals was used binary logistic regression. The value of statistical significance was set at 5% or p <0.05 and confidence interval was 95% (95% CI). The homozygous and heterozygous mutant were analyzed and grouped into one group and compared with the homozygous wild for the gene studied. All statistical analysis was performed with the Statistical Package for Social Sciences, version 14.0. Results: With respect to quantitative variables, significant differences were observed for all (p <0.05), except for age of menopause. In the analysis of qualitative variables, we found that only significant difference for women who had a family history of prolapse. There was no statistically significant difference regarding the presence of the polymorphism in question in both groups, whereas the genotypes studied were in Hardy-Weinberg. Conclusion: The presence of a polymorphism in exon 31 of alpha chain 1 gene of collagen type 3 is not a risk factor for pelvic organ prolapse in the Brazilian population studied.